NGARUH PENAMBAHAN TEPUNG DAUN JAMBU BIJI DAN ARANG AKTIF PADA RANSUM PUYUH PETELUR (Coturnix coturnix japonica) TERHADAP KONDISI KESEHATAN MASA PUNCAK PRODUKSI - Laksono Yusak Dinun (Universitas Islam Balitar, 2023)
This study aims to determine the addition of guava leaf meal (JB) and activated charcoal (AA) to laying quail rations on health conditions during peak production. The material used was 240 female quails aged 90 days using the experimental method with a completely randomized design (CRD) 4 treatments 6 replicates, at P0 using 100% control feed, P1 (100% control feed + 0.5% JB + 0.5% AA), P2 (100% control feed + 0.5% JB + 1% AA), P3 (100% control feed + 1% JB + 0.5% AA). The variables observed were changes in body weight, mortality, excreta water content, percentage of eggshell abnormalities. This study showed that the combination of JB and AA in quail rations had no significant effect (P<0.5) on changes in body weight with the highest value at P3 (12.08 grams), mortality with the highest average at P2 (2.00% ), eggshell abnormalities with the highest average at P0 (1.20%). Significantly affected the quality of excreta water content at week 4 at P3 (43.62%) and week 6 at P3 (43.43%). The conclusion of this study is that there is a significant effect on excreta water content and no significant effect on PBB, mortality, eggshell abnormalities.